2015
DOI: 10.1039/c5cp03323c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of interfacial thermal transport between silicene and substrates

Abstract: In this work, the interfacial thermal transport across silicene and various substrates, i.e., crystalline silicon (c-Si), amorphous silicon (a-Si), crystalline silica (c-SiO2) and amorphous silica (a-SiO2) are explored by classical molecular dynamics (MD) simulations. A transient pulsed heating technique is applied in this work to characterize the interfacial thermal resistance in all hybrid systems. It is reported that the interfacial thermal resistances between silicene and all substrates decrease nearly 40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 51 publications
(87 reference statements)
3
34
1
Order By: Relevance
“…Significantly different, at the a‐Si/a‐Ge interface, this highly interacting frequency range of 12–13 THz shifts to a broader frequency range of vibrations around 10–14 THz, with all the vibrational modes in this wide range contributing approximately equally to the interfacial thermal transport. In addition, similar phenomena of lower thermal resistance at the amorphous interface than that at the crystalline interface was also found in the work of Zhang et al They studied the interfacial thermal transport across silicene and various substrates (c‐Si, a‐Si, c‐SiO 2 , and a‐SiO 2 ) using classical MD simulations. They found that the ITR decreases monotonically with temperature.…”
Section: Thermal Transport Across An Amorphous Interfacesupporting
confidence: 65%
“…Significantly different, at the a‐Si/a‐Ge interface, this highly interacting frequency range of 12–13 THz shifts to a broader frequency range of vibrations around 10–14 THz, with all the vibrational modes in this wide range contributing approximately equally to the interfacial thermal transport. In addition, similar phenomena of lower thermal resistance at the amorphous interface than that at the crystalline interface was also found in the work of Zhang et al They studied the interfacial thermal transport across silicene and various substrates (c‐Si, a‐Si, c‐SiO 2 , and a‐SiO 2 ) using classical MD simulations. They found that the ITR decreases monotonically with temperature.…”
Section: Thermal Transport Across An Amorphous Interfacesupporting
confidence: 65%
“…Since the only energy dissipation channel in the heterostructure is through the heated monolayer to the substrate, correlations between the temperature difference and energy evolution can be used to calculate the interfacial thermal resistance without the awareness of specific heat. This technique has been used in our research to study the interfacial thermal transport across graphene-h-BN [80], graphene-phosphorene [81], graphene-stanene [82], silicene-silicon [83], graphene-silicon [84] and graphene-copper [85] interfaces. Compared to the NEMD method, the transient technique focuses on the dynamic response of the hybrid system and therefore can greatly reduce the computation time.…”
Section: Transient Method: Numerical Pump-probementioning
confidence: 99%
“…The effects of strain, interface, defect, surface functionalization, and size on the thermal conductivity of silicene nanoribbons have attracted considerable attention in the last decade. [20][21][22][23] Despite extensive studies on the electronic and thermal features of silicene nanoribbons, minimal research has been devoted to date to the thermal (phonon) transport of silicene nanotubes (SNTs). 24 Previous studies have shown that isotope impurities provide a powerful technique to modulate the phonon-related properties of carbon nanotubes (CNTs), 25 graphene, 26 and silicon nanowires.…”
Section: Introductionmentioning
confidence: 99%